2013
DOI: 10.1007/s10120-013-0234-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and prognosis of signet ring cell carcinoma of the stomach

Abstract: Background Signet ring cell carcinoma (SRC) of the stomach is a histological type based on microscopic characteristics. Although the distinctive clinicopathological features of SRC have been reported, results are inconsistent and survival outcomes are uncertain. Methods We retrospectively studied 769 patients with gastric carcinoma who underwent gastrectomy in our institute from 1999 to 2009. Among them, 326 patients (42.4 %) had early gastric cancer (EGC) and 443 patients (57.6 %) had advanced gastric cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
108
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(133 citation statements)
references
References 22 publications
(38 reference statements)
12
108
2
3
Order By: Relevance
“…Thus, numerous studies from Asia have demonstrated that the SRC type was more frequently diagnosed at a later stage, with a higher proportion of such tumors invading subserosa (pT3) or serosa (pT4); a higher rate of lymph node metastasis is also seen for the SRC type [7,10,33,34]. Furthermore, unsuspected peritoneal carcinomatosis Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, numerous studies from Asia have demonstrated that the SRC type was more frequently diagnosed at a later stage, with a higher proportion of such tumors invading subserosa (pT3) or serosa (pT4); a higher rate of lymph node metastasis is also seen for the SRC type [7,10,33,34]. Furthermore, unsuspected peritoneal carcinomatosis Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Signet ring cell carcinoma is more common in gastrointestinal tumors that have different biological characteristics. Advanced signet ring cell carcinoma has long been thought to have a worse prognosis than other forms of gastric cancer due to a high risk of peritoneal metastasis [43]. Thus, exploring ROS1 and ALK rearrangements may lead to a breakthrough in the treatment of patients with signet ring cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…This histologic subtype is reported in up to 26% of gastric cancers [Taghavi et al 2012] and in about 2% of colorectal carcinomas [Kwon et al 2014]. In comparison with adenocarcinoma, SRC arising in the stomach or the colorectal site is more frequent in younger patients, in women and more likely to present at a more advanced stage of disease.…”
Section: Discussionmentioning
confidence: 99%